Ultrasonic-assisted preparation of α-Tocopherol/casein nanoparticles and application in grape seed oil emulsion - Libin Sun (Elsevier, 2021)
In this work casein (CN) was used as a carrier system for the hydrophobic agent α-tocopherol (α-TOC), and an amphiphilic self-assembling micellar nanostructure was formed with ultrasound treatment. The interaction mechanism was detected with UV–Vis spectroscopy, fluorescence spectroscopy, proton spectra, and Fourier transform infrared spectroscopy (FTIR). The stability of the nanoparticles was investigated by using typical processing and storage conditions (thermal, photo, 20 ± 2 °C and 4 ± 2 °C). Oil-in-water emulsions containing the self-assembled nanoparticles and grape seed oil were prepared, and the effect of emulsion oxidation stability was studied using the accelerated Rancimat method. The results indicated that the UV–Vis spectra of α-TOC/CN nanoparticles complexes were different for ultrasonic treatments performed with different combinations of power (100, 200, 300 W) and time (5, 10, and 15 min). The results of UV–Vis fluorescence spectrum data indicated that the secondary structure of casein changed in the presence of α-TOC. The nanoparticles exhibited the chemical shifts of conjugated double bonds. Interactions between α-TOC and casein at different molar concentrations resulted in a quenching of the intrinsic fluorescence at 280 nm and 295 nm. Moreover, by performing FTIR deconvolution analysis and multicomponent peak modeling, the relative quantitative amounts of α-helix and β-sheet protein secondary structures were determined. The self-assembled nanoparticles can improve the stability of α-TOC by protecting them against degradation caused by light and oxygen. The antioxidant activity of the nanoparticles was stronger than those of the two free samples. Lipid hydroperoxides remained at a low level throughout the course of the study in emulsions containing 200 mg α-TOC/kg oil with the nanoparticles. The presence of 100 and 200 mg α-TOC/kg oil led to a 78.54 and 63.54 μmol/L inhibition of TBARS formation with the nanoparticles, respectively, vs the free samples containing control after 180 mins.